Proposta de um gateway industrial de código aberto utilizando o protocolo Modbus TCP - Souza, Thiago Pinheiro de (2022)
This work consists in the development of an industrial Gateway concept that allows the monitoring of devices through the Modbus TCP protocol. The modules that make up the Gateway structure are developed in the Python programming language, in addition to commu- nication resources via Modbus protocol, the system architecture consists of a cloud database for storing the collected information and a mobile application developed for interaction with the user. The project aims to help automation studies and enable integration with industrial equipment in order to make the protocols understanding and their operation accessible and low- cost implementation. The results obtained demonstrate the steps of connecting a device to a database in the cloud that captures the reading data through the Modbus TCP protocol.